Effect of environmental enrichment on relapse rates in patients with severe alcohol use disorder: protocol for a randomised controlled trial - Lila Barillot; Claudia Chauvet; Marc Besnier; Nematollah Jaafari; Marcello Solinas; Armand Chatard (BMJ Open)
Introduction Alcohol use disorder (AUD) ranks among the most prevalent psychiatric disorders worldwide. Despite current treatments, more than half of patients relapse within weeks after treatment. In animal models, exposure to environmental enrichment (EE) has been shown to be a promising approach to reduce relapse. However, controlled, multimodal EE is difficult to transpose to humans. To address this gap, this study aims at assessing the effectiveness of exposure to a newly designed EE protocol during AUD treatment in reducing relapse to alcohol use. Our EE will allow an enhancement of the standard intervention, and will combine several promising enrichment factors identified in the literature—physical activity, cognitive stimulation, mindfulness and virtual reality (VR).Methods and analysis A randomised controlled trial involving 135 participants receiving treatment for severe AUD will be conducted. Patients will be randomised to an intervention enhancement group or a control group. The enhanced intervention will consist of six 40-min sessions of EE spread over 9 days. During the first 20 min of these sessions, patients will practise mindfulness in multisensory VR, in virtual environments designed to practise mindfulness and use it to regulate craving induced by virtual cues or stress. Then, participants will practise indoor cycling combined with cognitive training exercises. The control group will undergo standard management for AUD. The primary outcome is relapse assessed at 2 weeks after treatment, using a questionnaire and biological indicators. Relapse will be defined as drinking at least five drinks per occasion or drinking at least five times a week. It is predicted that the group receiving the EE intervention will have a lower relapse rate than the control group. The secondary outcomes are relapse at 1 month and 3 months after treatment, craving and drug-seeking behaviour, mindfulness skills acquisition and the effect of the intervention enhancement on the perceived richness of the daily environment, assessed by questionnaires and neuropsychological tasks.Ethics and dissemination All participants have to give written informed consent to the investigator. This study is approved by the Ethics Committee Nord Ouest IV of Lille (reference number 2022-A01156-37). Results will be disseminated through presentations, peer-reviewed journals and seminar conferences. All information on ethical considerations and open science practices can be accessed at https://osf.io/b57uj/Trial registration number NCT05577741.